(untitled) (Palíndromo, 2018)
This article analyzes the relationship between Christian culture and the perspective form in the work of Masaccio during the first Renaissance, based on an interpretation of the Ita-lian historian Giulio Carlo Argan. For this reason, the theological debate of the total form present in St. Peter Damian’s writings is discussed in order to speculate interpretative possibilities for the emergence of perspective form in Florence in the 15th century. Other historians such as Frederick Antal, Ernst Gombrich, Ernst Panofsky are asked to dialogue with Argan’s interpretation. Thus, the essay follows two paths: 1st - it presents a work by Masaccio in the context of the Renaissance, and 2nd - it debates on the historiographic method of the Italian historian.